Molecular Dissection of Variation in Carbohydrate Metabolism Related to Water-Soluble Carbohydrate Accumulation in Stems of Wheat - Xue, Gang-Ping; McIntyre, C. Lynne; Jenkins, Colin L.D; Glassop, Donna; van Herwaarden, Anthony F; Shorter, Ray (Plant physiology (Bethesda), 2008)
Water-soluble carbohydrates (WSCs; composed of mainly fructans, sucrose [Suc], glucose [Glc], and fructose) deposited in wheat (Triticum aestivum) stems are important carbon sources for grain filling. Variation in stem WSC concentrations among wheat genotypes is one of the genetic factors influencing grain weight and yield under water-limited environments. Here, we describe the molecular dissection of carbohydrate metabolism in stems, at the WSC accumulation phase, of recombinant inbred Seri/Babax lines of wheat differing in stem WSC concentrations. Affymetrix GeneChip analysis of carbohydrate metabolic enzymes revealed that the mRNA levels of two fructan synthetic enzyme families (Suc:Suc 1-fructosyltransferase and Suc:fructan 6-fructosyltransferase) in the stem were positively correlated with stem WSC and fructan concentrations, whereas the mRNA levels of enzyme families involved in Suc hydrolysis (Suc synthase and soluble acid invertase) were inversely correlated with WSC concentrations. Differential regulation of the mRNA levels of these Suc hydrolytic enzymes in Seri/Babax lines resulted in genotypic differences in these enzyme activities. Down-regulation of Suc synthase and soluble acid invertase in high WSC lines was accompanied by significant decreases in the mRNA levels of enzyme families related to sugar catabolic pathways (fructokinase and mitochondrion pyruvate dehydrogenase complex) and enzyme families involved in diverting UDP-Glc to cell wall synthesis (UDP-Glc 6-dehydrogenase, UDP-glucuronate decarboxylase, and cellulose synthase), resulting in a reduction in cell wall polysaccharide contents (mainly hemicellulose) in the stem of high WSC lines. These data suggest that differential carbon partitioning in the wheat stem is one mechanism that contributes to genotypic variation in WSC accumulation.